脱式计算(能简算的要简算). 49×
2-
|
(1)49×
,5 46
=(46+3)×
,5 46
=46×
+3×5 46
,5 46
=5+
,15 46
=5
;15 46
(2)
+1 6
×3 4
÷2,2 3
=
+1 6
×3 4
×2 3
,1 2
=
+1 6
,1 4
=
+2 12
,3 12
=
;5 12
(3)
÷4 5
-80%×7 11
,4 7
=
×4 5
-11 7
×4 5
,4 7
=(
-11 7
)×4 7
,4 5
=1×
,4 5
=
;4 5
(4)2-
÷6 13
-9 26
,2 3
=2-
×6 13
-26 9
,2 3
=2-
-4 3
,2 3
=2-(
+4 3
),2 3
=2-2,
=0;
(5)(
+3 7
)×42-1 17
,8 17
=(
×42+3 7
×42-1 17
,8 17
=18+
-42 17
,8 17
=18+(
-42 17
),8 17
=18+2,
=20;
(6)(
-1 3
)÷1 4
+1 2
,5 6
=(
-4 12
)÷3 12
+1 2
,5 6
=
×2+1 12
,5 6
=
+1 6
,5 6
=1.